Older adults' provision of informal care and support to their peers – A cornerstone of swedish society: Demographic characteristics and experiences of social isolation. Issue 2 (30th December 2021) - Siira, Elin; Olaya‐Contreras, Patricia; Yndigegn, Signe; Wijk, Helle; Rolandsson, Bertil; Wolf, Axel
Abstract: Background: Family members provide the majority of informal care for older adults in Sweden. Nevertheless, by providing a range of assistance, peers often emerge as a central to counter social isolation among older adults. Therefore, there is a need to know more about what informal care provision by older adults to their peers means for different groups of older adults. Aim: This study investigated the types of informal care and support that older adults provide to their peers in Sweden, and how these types of care and support are associated with demographic characteristics and social isolation. We also compared older adults who provide informal care and support with those who do not. Method: For this purpose, we used a national online survey named "Involuntary loneliness among senior citizens" answered by 10, 044 older adults enrolled in the Swedish Citizen Panel. We adopted a mixed‐method design to analyse the survey data, including free‐text options ( n = 2155) and numerical data. Social isolation was assessed using a score built from the social loneliness items of the UCLA Loneliness Scale. Results: In our population, 21.5% of the older adults were providing informal care and support to their peers. Practical/instrumental help was frequently offered by younger participants (<75 years), men and respondents who were less socially isolated. On a general level, the factors that were positively associated with giving informal care and support to peers were older age, being male, retired, married/living in a relationship, living in an urban area/big city and exhibiting greater isolation. Focusing specifically on social support shows that older participants (>80) and those experiencing less social isolation (score < 24) were more engaged in social activities. Conclusion: This paper is unique in exploring the informal peer‐caregiver's perceptions of isolation. Data were collected during the COVID‐19 pandemic; this highlights the need to recognise informal care and support between older adults and to acknowledge their contributions as an essential component of Swedish civil society, especially during a societal crisis.